1980
DOI: 10.1093/chromsci/18.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Trace Analysis of Potentially Carcinogenic Metabolites of an Azo Dye and Pigment in Hamster And Human Urine as Determined by Two Chromatographic Procedures

Abstract: Analytical chemical procedures are described for determining traces of possible metabolites of two azo compounds. Direct Black 38 and Pigment Yellow 12, in hamster urine and to monitor the urine from workers who may be occupationally exposed during the manufacture or use of the dye and pigment. These methods were required for metabolism studies designed to assess the hazards that may occur if the two compounds are converted by in vivo mechanisms to potential carcinogens. Salient elements of the procedure are: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Azo dyes give bright, high-intensity colors, much more so than the next most common dye class, anthraquinones [1][2][3][4]. The toxicity and carcinogenic nature of these dyes and their predecessors pose a threat to the environment [5][6][7][8][9]. Lethal levels may be reached, affecting aquatic systems and associated flora and fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes give bright, high-intensity colors, much more so than the next most common dye class, anthraquinones [1][2][3][4]. The toxicity and carcinogenic nature of these dyes and their predecessors pose a threat to the environment [5][6][7][8][9]. Lethal levels may be reached, affecting aquatic systems and associated flora and fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies with rats, dogs, and hamsters have shown that animals administered BZ and BZ-congenerbased dyes excrete potentially carcinogenic aromatic amines and their N-acetylated derivatives in their urine (12,19,20). Also , when anaerobic bacterial suspensions isolated from monkey and rat feces and intestinal contents as well as from human feces were incubated with BZ and BZ-congenerbased dyes, reduction of the dyes and formation of their respective free amines were observed (4).…”
mentioning
confidence: 99%
“…Kewujudan pewarna organik sintetik dalam efluen walaupun hanya dalam kuantiti yang kecil dikatakan dapat mempengaruhi nilai estetik, kerana pewarna yang dihasilkan ini mempunyai warna yang sangat kuat. Selain itu juga, pewarna organik sintetik yang dihasilkan biasanya menggunakan bahan kimia yang toksik dan bersifat karsinogenik terhadap ekosistem akuatik dan kehidupan manusia secara amnya (Manning et al 1985;Nony & Bowman 1980). Kewujudan pewarna organik sintetik di dalam efluen merupakan satu perkara yang tidak diingini.…”
Section: Pengenalanunclassified